1996
DOI: 10.1046/j.1365-2648.1996.02135.x
|View full text |Cite
|
Sign up to set email alerts
|

Health within illness: experiences of chronically ill/disabled people

Abstract: The concept of health within illness is beginning to gain recognition in nursing. However, there has been little research to explore and describe this phenomenon. The results of a recent study investigating the meaning of the experience of feeling healthy for people living with a chronic illness and/or disability are presented. An interpretive phenomenological study was undertaken with eight participants living with a variety of different chronic conditions. The results provide a rich mosaic of themes describi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 15 publications
1
92
0
1
Order By: Relevance
“…The present study identified the importance of being able to contribute to otherspartners, assistants, families, friends and communities -in reciprocal relationships that foster perceptions of value and competence, connecting and belonging, a finding supported by other researchers. 1,32,33,73,[77][78][79][80][81][82][83][84][85] The important role that special people had played in encouraging autonomy, affirming value and worth and facilitating engagement in meaningful occupations suggests that the rehabilitation process would benefit from the conscious and deliberate inclusion of friends and families. If relationships with special people provide opportunities for reciprocity and for engaging in meaningful occupations following discharge it makes little sense to exclude these people from the rehabilitation process.…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified the importance of being able to contribute to otherspartners, assistants, families, friends and communities -in reciprocal relationships that foster perceptions of value and competence, connecting and belonging, a finding supported by other researchers. 1,32,33,73,[77][78][79][80][81][82][83][84][85] The important role that special people had played in encouraging autonomy, affirming value and worth and facilitating engagement in meaningful occupations suggests that the rehabilitation process would benefit from the conscious and deliberate inclusion of friends and families. If relationships with special people provide opportunities for reciprocity and for engaging in meaningful occupations following discharge it makes little sense to exclude these people from the rehabilitation process.…”
Section: Discussionmentioning
confidence: 99%
“…Common themes include: rethinking one's priorities and commitments given a sense of limited time; an amplified sense of mortality and fragility; a reawakened appreciation of the good things in one's life, and privileging the present (Frank 2002). In illness priorities often change and it is an opportunity to consider how one has lived and how one would like to live (Lindsey 1996;Lindqvist et al 2006). The ill person may radically revise what she thinks of as optimal use of time.…”
Section: Space and Timementioning
confidence: 99%
“…However, chronic illnesses may also include positive aspects like developing new meaningful lives, creating new opportunities, self-development, and control over everyday life (5,(11)(12)(13). It became obvious that what the respondents did in everyday life could be interpreted in terms of reversing symptoms and normalizing everyday life situations.…”
Section: Introductionmentioning
confidence: 99%